1993
DOI: 10.1128/mcb.13.4.2391
|View full text |Cite
|
Sign up to set email alerts
|

The sites of phosphorylation by protein kinase C and an intact SH2 domain are required for the enhanced response to beta-adrenergic agonists in cells overexpressing c-src.

Abstract: Previously we demonstrated that C3H1OT½ murine fibroblasts overexpressing avian c-src exhibit elevated levels of cyclic AMP (cAMP) in response to 13-adrenergic believed to be important for signalling processes. In this study we show that the sites of phosphorylation by protein kinase C (PKC) (Ser-12 and Ser-48) as well as the SH2 region of pp60C are required for the enhanced response of c-src overexpressors to 13-agonist stimulation. Mutation at the site of myristylation (Gly-2) results in a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…We used three Src mutants: (1) Y527F c-Src (constitutively-active) (Cartwright et al, 1987); (2) K297M Src (kinase-inactive) (Snyder et al, 1985); and (3) dl155 Src (contains a three amino acid deletion in the phosphotyrosine binding pocket of the SH2 domain) (Moyers et al, 1993). Previously, we showed that the dl155 Src mutant has reduced binding to RACK1 (Chang et al, 2001).…”
Section: Rack1 Is An Endogenous Substrate For Srcmentioning
confidence: 99%
See 1 more Smart Citation
“…We used three Src mutants: (1) Y527F c-Src (constitutively-active) (Cartwright et al, 1987); (2) K297M Src (kinase-inactive) (Snyder et al, 1985); and (3) dl155 Src (contains a three amino acid deletion in the phosphotyrosine binding pocket of the SH2 domain) (Moyers et al, 1993). Previously, we showed that the dl155 Src mutant has reduced binding to RACK1 (Chang et al, 2001).…”
Section: Rack1 Is An Endogenous Substrate For Srcmentioning
confidence: 99%
“…Plasmids encoding wild-type (pM5H) or mutant dl155-157 (pM155) chicken c-src were gifts from Sarah Parsons (University of Virginia, Charlottesville, VA, USA; Moyers et al, 1993). pGEM K297M src was a gift from Tony Hunter (The Salk Institute for Biological Studies, La Jolla, CA, USA; Snyder et al, 1985).…”
Section: Plasmidsmentioning
confidence: 99%
“…The PKC activity is regulated by its translocation to the membrane and phosphorylation and generally denotes enzyme activation (334). PKC is the target for multiple tyrosine phosphorylations by various tyrosine kinases, including Src family kinases (304,396). These modifications further increase kinase activity of PKC (243).…”
Section: Pkcsmentioning
confidence: 99%
“…Early studies with murine fibroblasts stably overexpressing wildtype avian c-Src showed that stimulation of the b adrenergic agonist isoproterenol resulted in a threefold increase in cAMP levels relative to that induced in nontransfected cells or cells expressing catalytically inactive Src (Bushman et al, 1990. The enhanced response to b-agonists requires both an intact Src SH2 domain and the presence of Ser-12 and Ser-48, sites of PKC phosphorylation in the kinase (Moyers et al, 1993). In vitro analysis suggests that Src affects G-protein regulation of adenylyl cyclase at two points, a stimulatory effect at the level of G-protein activation, and a modest inhibitory effect at the level of adenylyl cyclase itself.…”
Section: Src Family Kinase Regulation By Heterotrimeric G Proteinsmentioning
confidence: 99%